Effectiveness of a community based physical activity intervention grounded in motivational interviewing. (November 2018) - Wade, Matthew; Brown, Nicola; Majumdar, Anne
Abstract: Introduction: Active lifestyles can manage and prevent over 20 chronic conditions, reducing the burden on health services. Yet, ensuring that at-risk groups are sufficiently active is a major public health challenge. Behaviour change interventions exist within primary care to support adults increase their physical activity (PA), with the National Institute for Health and Care Excellence recommending brief advice to elicit positive change. The aim of this study was to assess whether the effectiveness of a community-based PA intervention grounded in motivational interviewing can influence change in PA and mental wellbeing. Methods: Participants from the county of Essex, UK, were invited to take part in a community-based PA programme (Let's Get Moving), which uses motivational interviewing techniques; they were eligible if according to general practice records they were 18–74 years old, with a body-mass index of 28–35 kg/m 2 . An initial 30 min motivational interviewing appointment was conducted at baseline, relevant activities signposted, and data collected. 12 week data were collected during a face-to-face follow-up, and 6 month and 12 month data were collected via telephone. Self-reported PA levels were collected using the International Physical Activity Questionnaire (IPAQ), and mental wellbeing using the Short Warwick Edinburgh Mental Wellbeing Scale (SWEMWBS). Good reliability exists between face-to-face and telephone-administered IPAQ, but is unknown between approaches for the SWEMWBS. Findings: 2084 individuals attended the programme (1117 [60·9%] women, mean age 61·3 years [SD 11·7], 1780 [95·1%] White or White British, 1415 [67·9%] with a disability). Retention (participants who provided data) decreased over time (1239 [59·5%] at 12 weeks, 959 [46·0%] 6 months, 764 [36·7%] 12 months). Paired-samples t test revealed significant (all p<0·0001) increases in vigorous and moderate intensity PA, walking, and total PA at 12 weeks (n=1239), 6 months (n=959) and 12 months (n=764). Paired-samples t test revealed statistically significant (p<0·0001) increases in mental wellbeing at 12 weeks (n=401), 6 months (n=168), and 12 months (n=160), above the English average (SWEMWBS score 23·6). Effect size (0·3–0·8) and power (1·0) were good. Interpretation: Initial and longitudinal findings indicate that a PA intervention grounded in motivational interviewing produces significant improvements in physical and mental health. The data inform the development of future delivery of brief interventions. However, because of the nature of the study there is a high risk of bias and confounding variables that could affect the results, which limits interpretation. Funding: None.